The Influence of Emotional Labor and Emotional Intelligence on Job Performance: does ownership structure matter? - A Comparison of Public and Private Organizations in China - Ma, S.; Silva, M. G.; Trigo, V.; Callan, V. J. (The Ninth International Symposium on Multinational Business Management-- Entrepreneurship, Organizational Change and Employment Management, 2017)
Purpose–This research addresses two main questions: (1) whether emotional labor varies among organizations with different ownership structures; and (2) whether emotional labor and emotional intelligence relate to job performance in different ways in public and private organizations. Methodology– Data were collected through self-report questionnaires (n=306), targeting a specific group of managers and professionals working for the public sector, domestic privately owned enterprises and foreign firms in China. Findings – (1) Significant differences were found in the emotional labor reported in public and private organizations; (2) emotional labor was found to have a significant effect on in-role performance while emotional intelligence moderated the link between emotional labor and job performance. However this moderation effect was not found in private organizations, but only in public ones. Limitations– The different sample sizes for ownership types presents one research limitation. Other limitations are the cross-sectional design and a potential common methods bias. Implications for practice – (1) The relationships among emotional labor, emotional intelligence and job performance may vary depending on the organizational context like the ownership type; (2) as it was found that organizations of different ownership types may exhibit different levels of emotional labor, both employers and employees might benefit from this research when considering the issue of person-organization fit. 3. Organizations should employ humanistic HRM practices to create positive work environment to mitigate the costs of emotional labor. Originality –1. These findings identify ownership type as a new antecedent of emotional labor. The study moves beyond the focus on occupational group or work unit to organizational ownership type, and builds further upon our understanding of the organizational context in shaping emotional labor. 2. Results imply that ownership structure is a potential “social group” variable in emotional labor studies. 3. The study also focuses on managerial professionals in the context of China whereas conventional research on emotional labor has been more concentrated on frontline service workers.